ROLE OF THE JUVENILE SOURCES OF ORE COMPONENTS IN URANIUM ORE GENESIS OF PRIAZOVYE - KALASHNYK, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The spatial, time and geochemical relationship between the formation of uranium ore objects and alkaline-ultrabasic magmatism in the Priazovsky megablock and in adjacent territories have been considered in the paper. The analysis of the uranium content in crystalline rocks of Priazovje, in the basal strata of eyfelskie sediments which surrounding stratiform uranium ore bodies in the junction zone between the Priazovsky megablock and Donbas and in the space-time-associated with uranium ore process kimberlitic magmatism are given in the paper. The influence of mantle processes for uranium ore genesis in the region investigated. This results can be instrument in the increase of efficiency and purposefulness in prognosis-searching and exploration geological works.